PULANG KAMPUNG KE GONGJIN: TRAUMA DAN MIMPI HONG DU-SHIK DALAM HOMETOWN CHA-CHA-CHA: (PSIKOANALIS FREUD) - Atari Dian Pratiwi Atari (Mahakarya: Jurnal Mahasiswa Ilmu Budaya, 2023)
Generally, a romantic love story with psychological nuances becomes the marking theme in Korean drama. Using the themes is a strategy so Korean dramas stay in the market and keep providing viewers with fresh images. DramaHometown Cha-Cha-Cha(2021) is interesting because the main character experiences severe trauma yet still stands back for his life. This article discussed the phenomenon using Sigmund Freud. The approach used was a Freudian analysis model with a qualitative descriptive method. The aim of the study was to explain (a) the trauma that affects the main character’s personality and (b) the roles of the id, ego, and superego in the character’s behavior. The results showed that the personality of the main character, Du-Shik, was described as kind, helpful, friendly, romantic, and warm, but he has a very heavy trauma. Since he was young, Du-Shik was abandoned by the people he loved, and he felt that he had failed to help a security guard and caused a friend’s death. The trauma he experienced affects his personality and life, such as frequent nightmares because of excessive guilt, fear, and anxiety. The research finding also revealed that the main character’s id was presented through the emergence of pity, comfort, love, fear, and nightmares. The ego was presented through the use of common sense, contemplation, and speechlessness in making decisions, while the superego was represented with a willingness to tell stories and dare to love the leading female character, Hyejin, back. Key words: Hometown Cha-Cha-Cha, trauma, nightmare, Sigmund Freud’s psychoanalysis